PENANGGULANGAN KEKERASAN DALAM RUMAH TANGGA DALAM PANDANGAN MASYARAKAT KABUPATEN MALUKU TENGAH - Jamaa, La; Lateni, Anwar (TAHKIM, 2018)
Even though the government has enacted Law Number 23 of 2004 concerning the Elimination of Domestic Violence, domestic violence continues to occur in the community. Because it requires community involvement. In this regard the muslim community of Salahutu sub-district, Leihitu and West Leihitu Central Maluku regency have their own solutions in dealing with violence in the intended household through the utilization of local wisdom called saudara kawin (brother married). Brother married are able to overcome the problems of the married sister’s household problem, including preventing the husband from committing violence to his wife. So there is no need for efforts to combat domestic violence at the repressive stage by law enforcement.